Rhabdomyolysis with erratic serum creatinin phosphokinase levels: intramuscular injection of haloperidol decanoate - Karre, Premnath Reddy (BMJ Publishing Group, 2009)
A 56-year-old African American female with a history of schizophrenia developed rhabdomyolysis with creatine phosphokinase (CPK) levels of 5172 U/L after intramuscular injection of haloperidol decanoate. The patient was admitted to the hospital and treated with saline infusion alone. Serum CPK levels were decreased but not significantly so even after 4 days. Renal function tests and vital signs remained normal throughout her stay in the hospital. Urinary alkalinisation was done with sodium bicarbonate to maintain urine pH higher than 6.5 and the CPK levels declined gradually over the next 3 days. The patient was observed for 24 hours without saline infusion and urine alkalinisation but the serum CPK levels continued to increase and this regimen was restarted. The patient stayed in the hospital for 4 weeks on this regimen until the CPK levels decreased and remained normal. Our patient developed rhabdomyolysis without neuroleptic malignant syndrome.